Influence of energy drinks on obesity: a preliminary experimental study - Mattioli, Anna Vittoria; Pennella, Sonia; Manenti, Antonio; Ballerini Puviani, Matteo; Farinetti, Alberto (Progress in Nutrition, 2018)
We performed an experimental research in Sprague-Dawley rats in order to evaluate the effects of different caffeinated beverages on obesity. Animals were divided in 4 groups and received beverages containing different concentration of caffeine: a commercial Energy Drink, a commercial Cola Soda, regular coffee and water. After 15 days we found that Energy Drink and Cola Soda induced body weight gain, on contrary sweetened coffee and water did not influence weight. Besides, an increased reactivity and motility was observed in the Energy Drink supplemented animals. Laboratory tests excluded obesity-correlated dysmetabolism. We supposed a central nervous action of some components of Energy Drink other than caffeine, even if their finest mechanisms are unknown. At long term, degeneration from a condition of body weight gain to obesity cannot be excluded.